Soybean Cost-Return Budget in North Central Kansas - Dumler, Troy J.; Duncan, Stewart R. (My University, 2005)
This publication provides estimated cost and returns for forward farm planning for soybeans in north central Kansas.
MF2160_2005_10
Keywords: MF2160; Crops; Economics; MF